2017
DOI: 10.3174/ajnr.a5039
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Atrophy Is Associated with Altered Hippocampus–Posterior Cingulate Cortex Connectivity in Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis

Abstract: BACKGROUND AND PURPOSE:Unilateral mesial temporal lobe epilepsy and hippocampal sclerosis have structural and functional abnormalities in the mesial temporal regions. To gain insight into the pathophysiology of the epileptic network in mesial temporal lobe epilepsy with hippocampal sclerosis, we aimed to clarify the relationships between hippocampal atrophy and the altered connection between the hippocampus and the posterior cingulate cortex in patients with mesial temporal lobe epilepsy with hippocampal scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Notwithstanding the current view of focal epilepsy as a network disorder, there is increasing evidence for complex interactions between local function, structural pathology and whole-brain connectivity (Bernasconi, 2017). In temporal lobe epilepsy, numerous studies have shown decreased functional connectivity of the ipsilateral hippocampus (Bettus et al, 2009;Maccotta et al, 2013;Morgan et al, 2015), especially with the default mode network (Kucukboyaci et al, 2013), the severity of which scales with hippocampal pathology (Bernhardt et al, 2016;Shih et al, 2017). Conversely, in FCD, while individual analyses indicate altered local function and connectivity, as well as brain-wide alterations across patients (Stufflebeam et al, 2011;Lee et al, 2014;Besseling et al, 2016;Hong et al, 2017b;Jackson et al, 2017;Gupta et al, 2018), no study has so far tackled grouplevel connectivity from a lesion perspective and its relationship to the structural pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the current view of focal epilepsy as a network disorder, there is increasing evidence for complex interactions between local function, structural pathology and whole-brain connectivity (Bernasconi, 2017). In temporal lobe epilepsy, numerous studies have shown decreased functional connectivity of the ipsilateral hippocampus (Bettus et al, 2009;Maccotta et al, 2013;Morgan et al, 2015), especially with the default mode network (Kucukboyaci et al, 2013), the severity of which scales with hippocampal pathology (Bernhardt et al, 2016;Shih et al, 2017). Conversely, in FCD, while individual analyses indicate altered local function and connectivity, as well as brain-wide alterations across patients (Stufflebeam et al, 2011;Lee et al, 2014;Besseling et al, 2016;Hong et al, 2017b;Jackson et al, 2017;Gupta et al, 2018), no study has so far tackled grouplevel connectivity from a lesion perspective and its relationship to the structural pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple causative factors have been implicated in the development of human mTLE/HS, including febrile seizures, brain trauma, inflammatory brain conditions, as well as genetic and epigenetic factors; it is likely that many cases may be multifactorial with regard to cause ( 15 19 ). Regardless of cause, the abnormal hippocampus is structurally and functionally connected to the adjacent mesial temporal lobe, and these structures are believed to develop an epileptic circuit ( 20 ). MRI can detect focal changes in brain architecture that can provide clues regarding etiology and treatment; this is visible as a change in the volume of a given region of the brain ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ictal propagation to the cingulate gyrus has frequently been observed among patients with temporallobe epilepsy [18].However,YCShih found in patients with left mesial temporal lobe epilepsy with hippocampal sclerosis, the left inferior cingulum bundle underwent degeneration in tandem with the left hippocampus volume, whereas intrinsic functional connectivity seems to react by compensating for the loss of connectivity. Their results suggested that increased intrinsic functional connectivity of the contralesional hippocampus was a compensatory response to decreased hippocampal connectivity on the lesion side [23].According to the hypothesis, we speculate that the PCG lesion and hippocampus functional connectivity decreased,but the contralesional PCG and hippocampus have extensive unctional connections. Fundamental to the original concept of the EZ was the idea of one or more regions of brain involved in the primary organization of the ictal discharge, rather than a ''focus''.Indeed, from the outset of SEEG development, the EZ was seen as a set of interconnected regional systems [24].…”
Section: Discussionmentioning
confidence: 59%